Scalable Online Learning in Physical Chemistry - Michael A. Nash (CHIMIA, 2021)
The SARS-CoV-2/COVID-19 pandemic has disrupted higher education across the globe. As of early November 2020, Europe now finds itself in the middle of a second wave that is even more destructive than the first. The Swiss Federal Council declared on 28 October, 2020 that face-to-face teaching at Swiss Universities was to cease within days. With large introductory lectures in natural science faculties forced entirely online, educators in Switzerland are facing new challenges and dealing with the limitations of remote instruction. Through a series of anecdotes and observations, this article identifies challenges associated with scalable online learning, and explores methods to mitigate them. Additionally, several advantages to scalable online instruction are identified. By focusing on areas where online instruction has significant advantages, I argue that we can deliver high quality instruction in the chemical sciences remotely.